Profiling of Blood-Brain Barrier Disruption in Mouse Intracerebral Hemorrhage Models: Collagenase Injection vs. Autologous Arterial Whole Blood Infusion - Jia, Peijun; He, Jinxin; Li, Zefu; Wang, Junmin; Jia, Lin; Hao, Ruochen; Lai, Jonathan; Zang, Weidong; Chen, Xuemei; Wang, Jian (Frontiers in Cellular Neuroscience, 2021)
Disruption of the blood-brain barrier (BBB) and the subsequent formation of brain edema are the most severe consequences of intracerebral hemorrhage (ICH) that leads to drastic neuroinflammatory responses and neuronal cell death. The collagenase injection and autologous arterial whole blood infusion models have been developed to analyze BBB breakdown after ICH. However, it remains unclear that whether the temporal progression and the mechanism of BBB breakdown are similar between these two models. In this study, we determined the progression and the mechanism of BBB disruption in two these most widely used murine ICH models: the collagenase-induced ICH model (c-ICH) and the double autologous whole blood ICH model (b-ICH). We matched the initial hematoma volume in these two models, analyzed BBB permeability using Evan's blue and IgG extravasation, and observed tight junction (TJ) damage by transmission electron microscope (TEM) and Western blotting. Matrix metalloproteinase-9 (MMP-9) activity and aquaporin 4 (AQP4) mRNA expression were also detected by Gelatin gel zymography and RT-PCR. The results showed that the severe BBB leakage associated with decreasing TJ protein expression and increasing in MMP-9 activity and AQP4 expression occurred on day 3 in the c-ICH model whereas on day 5 in the b-ICH model. Additionally, using TEM, we observed that the TJ was greatly decreased on day 3 in the c-ICH group whereas on day 5 in the b-ICH group. In conclusion, in both ICH models, the degree of BBB breakdown appeared basically equivalent after ICH which can both used in preclinical research. However, the collagenase model presented with more pronounced disruption of BBB at earlier time points than the blood ICH model, suggesting that c-ICH models may be more suitable for studying BBB damage mechanism than b-ICH models.